Time and Timelessness - Mahadevan, T. M. P. (Journal of Dharma, 1976)
The various definitions of "Time" may be classified into three different, broad types-the definitions of the mathematical physicist, of the psychologist, and of the metaphysician. The physicist is interested in the quantitative measurement of time in terms of logical relation of before-and-after, expressed in numbers. To him, time is a homogeneous continuum. Measurement requires a constant and standard unit. The difficulty in measuring time is that it "passes away". It is not possible to place intervals of time side by side and compare them, because the intervals are successive and not simultaneous. The sun serves as the standard of reference for measuring time and thus day and night, seasons, etc., are all measured with reference to the sun. For a wider field than the solar system, the velocity of light serves as the standard. Without resorting to signs, marks or signals in space, it is not possible to measure time. It is obvious that time measurement is relative, based on arbitrary standards. Einstien’s theory of relativity has brought forth many paradoxes involved in the example of a man travelling in space with a speed either less or greater than that of light. In that case, mathematically, a man’s death should occur before his birth. Further, time has been proved by the relativity theorist as the fourth dimension, and hence every point is a ’spacetime’ point instead of a three dimensional space point.